Women News Coverage in a Malaysian and an Indonesian Daily Newspapers in 1999 - Ginting, Rahmanita (2002)
Coverage of women news represented in the newsworthiness determinants, news categories, the usage of photo and space measurement taken from the developing countries' perspective comprise an area that has not been thoroughly investigated. Hence, a study on women news coverage needs to be undertaken. The objective of the study was specifically to determine (1) The newsworthiness determinants of Malaysian and Indonesian daily newspapers on news covering women (2) The identification and comparison the news categories in the women news covered by the Malaysian and Indonesian daily newspapers (3) The comparison of illustration of photo in news in terms of measurement and proportion of space taken by women news item with photo between Malaysian and Indonesian daily newspapers. A constructed week method was applied in sampling the population, which comprised of 149 women news articles published between January 1st - December 31 1st 1999 by the Utusan Malaysia (Malaysia) and the Kompas (Indonesia) newspapers. Statistical procedure employing the Statistical Package for Social Sciences (SPSS) was used for data analysis. Specifically, descriptive statistics such as frequencies and percentages were used. Most coverage of women news by two newspapers was concentrated in the special column news section. The study revealed that the standard newsworthiness determinants were considered but at varying degrees in determining the coverage of women news. Prominence becomes the first rank on the news determinant list for the Utusan Malaysia and Kompas newspapers. The study found that news categories were substantial however some categories were published more than the others. Culture and arts represented the highest number of news categories on women news covered by Utusan Malaysia and Kompas. The findings also showed that more than half of total women news coverage enclosed with photo.